Based on mobile RFID for membership stores system conforming EPC C1G2 standards. (13th September 2012) - Chen, Chin–Ling; Chien, Chih–Feng
In this paper, we propose a novel scheme conforming to EPC C1G2 standards with low implementation cost. Benefit from reducing the manpower of market management, the market members can use the mobile reader to query products information and make a secure transaction through cash register efficiently. The membership holders can also use the accumulated digital coupons to redeem prizes with the server. Moreover, in order to achieve the mutual authentication, the proposed scheme integrates the fingerprint biometrics, related cryptology and hash function mechanism to ensure the security of the transmission messages. It is also beneficial to M–commerce and can resist known attacks.